2013
DOI: 10.1186/2046-4053-2-115
|View full text |Cite
|
Sign up to set email alerts
|

The comparative recall of Google Scholar versus PubMed in identical searches for biomedical systematic reviews: a review of searches used in systematic reviews

Abstract: BackgroundThe usefulness of Google Scholar (GS) as a bibliographic database for biomedical systematic review (SR) searching is a subject of current interest and debate in research circles. Recent research has suggested GS might even be used alone in SR searching. This assertion is challenged here by testing whether GS can locate all studies included in 21 previously published SRs. Second, it examines the recall of GS, taking into account the maximum number of items that can be viewed, and tests whether more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 26 publications
3
94
0
1
Order By: Relevance
“…A majority of these studies conclude that although GS can be used as one of several bibliographic databases for literature retrieval, researchers should not use it as a stand-alone tool (Bramer, Giustini, Kramer, & Anderson, 2013;Giustini & Kamel Boulos, 2013). The authors of this study conclude otherwise, indicating that GS is sensitive enough to use as a stand-alone resource when performing systematic reviews.…”
Section: Commentarymentioning
confidence: 82%
“…A majority of these studies conclude that although GS can be used as one of several bibliographic databases for literature retrieval, researchers should not use it as a stand-alone tool (Bramer, Giustini, Kramer, & Anderson, 2013;Giustini & Kamel Boulos, 2013). The authors of this study conclude otherwise, indicating that GS is sensitive enough to use as a stand-alone resource when performing systematic reviews.…”
Section: Commentarymentioning
confidence: 82%
“…The main literature database searched was Google Scholar over the period January 1990 to May 2015 for pre-clinical animal studies and over the period January 2005 to May 2015 for clinical studies in humans. It has elsewhere been shown that Google Scholar provides a high degree of coverage and precision with regards to similar literature search engines, such as PubMed/MED [4]. To find clinical trials, the search strategy involved using terms such as "phase I trial" cataract where trial was replaced with study and clinical and the phase was varied.…”
Section: Methods: I) Systematic Literature Searchmentioning
confidence: 99%
“…Peer-reviewed literature as it is a common way to get access to the researchers" viewpoint whose selection is done using keywords based search. "Google Scholar" search engine is used for peer-reviewed papers as it is considered good and easy to operate source for public health related studies (Shariff et al 2013;Gehanno et al 2013;Shultz 2007) but, some cautions have been raised (Bramer et al 2013;Shultz 2007). The total of four levels of filtering mechanism is applied to shortlist journal papers for this study that lead to selection of 213 papers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%